2023
DOI: 10.1111/aab.12835
|View full text |Cite
|
Sign up to set email alerts
|

Low water supply differentially affects the growth, yield and mineral profile of kabuli and desi chickpeas (Cicer arietinum)

Abstract: The climatic events predicted to increase in intensity and frequency in the near future, including drought, may influence the quality and productivity of several important crops for human nutrition, such as legumes. Herein, two chickpea genotypes (Cicer arietinum) were analysed for their resilience to low water supply: a commercial white chickpea (kabuli) and a traditional black chickpea (desi) with marginal production in occidental countries. Plants were grown under four levels of water supplies (90%, 75%, 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 76 publications
0
0
0
Order By: Relevance
“…In our study, we also found significant differences between the two types of chickpea desi and kabuli . Several studies in pot and field experiments showed that desi was more tolerant to drought stress than kabuli 7 , 9 , 53 . Proline is considered an osmoprotectant as it maintains the osmotic potential and thus the turgor of the leaves.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, we also found significant differences between the two types of chickpea desi and kabuli . Several studies in pot and field experiments showed that desi was more tolerant to drought stress than kabuli 7 , 9 , 53 . Proline is considered an osmoprotectant as it maintains the osmotic potential and thus the turgor of the leaves.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, free proline and sugar helps to stabilize macromolecules and prevents oxidative damage 7 , 53 . Higher levels of minerals in desi serve as cofactors in various osmoregulatory and antioxidant mechanisms and also contribute to drought stress tolerance 9 .…”
Section: Discussionmentioning
confidence: 99%